Perawatan Pembesaran Gingiva dengan Gingivektomi - Andriani, Ika (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2009)
The purpose of this article is to report a case of treatment gingival enlargement by gingivectomy The inflammatory enlargement is clinically called hyperthropic gingivitis or gingival hyperplasia and generally related to local or systemic factors. They could be edematous or fibrous. The former is treated by scaling,curettage and root planing, but the latter could not be treated by scaling, curettage and root planing and only has to be removed by gingivectomy A 13-year-old female presented with a complaint of swelling of the gingiva with bled when brushed the teeth in the maxillary and mandibulary anterior region for a period of three mounts. A clinical examination revealed the existence of poor oral hygiene and bleeding spontaneously. By scaling, curettage and root planning this disease could not be treated and only has to be removed by gingivectomy. After gingivectomy, the patient had a better clinical appearance and good gingival esthetic.Tujuan penulisan naskah ini adalah melaporkan kasus perawatan pembesaran gingiva dengan gingivektomi Pembesaran gingiva karena peradangan secara klinis disebut gingivitis hipertropi atau hiperplasi gingival dan disebabkan karena faktor lokal ataupun sistemik. Bisa karena odematus atau fibrotik., jika tidak bisa dirawat dengan scaling, curettage dan root planing maka hanya dilakukan gingivektomi. Pasien wanita 13 tahun datang ke bagian Periodonsi RS Sudomo Universitas Gadjah Mada Yogyakarta dengan keluhan, sudah tiga bulan gigi-gigi anterior rahang atas dan bawah membesar dan berdarah ketika menyikat gigi. Pemeriksaan klinis kelihatan bahwa kebersihan mulut yang buruk dan berdarah spontan. Ketika pembesaran gingiva tidak dapat dirawat dengan scaling, curettage dan root planing maka hanya bisa dihilangkan dengan gingivektomi. Sesudah gingivektomi, pasien secara klinis dan estetik lebih baik